Pattern dependence in synergistic effects of total dose on single-event upset hardness - 郭红霞 丁李利 肖尧 张凤祁 罗尹虹 赵雯 王园明 (Chinese physics B, 2016)
The pattern dependence in synergistic effects was studied in a 0.18 μm static random access memory（SRAM） circuit.Experiments were performed under two SEU test environments：3 Me V protons and heavy ions.Measured results show different trends.In heavy ion SEU test,the degradation in the peripheral circuitry also existed because the measured SEU cross section decreased regardless of the patterns written to the SRAM array.TCAD simulation was performed.TIDinduced degradation in n MOSFETs mainly induced the imprint effect in the SRAM cell,which is consistent with the measured results under the proton environment,but cannot explain the phenomena observed under heavy ion environment.A possible explanation could be the contribution from the radiation-induced GIDL in pMOSFETs.